Culturable airborne bacteria and isolation of methicillin-resistant coagulase-negative staphylococci from outdoor environments on European side of Istanbul, Turkey - Sivri, Nuket; Bagcigil, Arzu Funda; Metiner, Kemal; Seker, Dursun Zafer; Orak, Selin; Durak, Sevgi Gunes; Sonmez, Vildan Zulal (POLSKA AKAD NAUK, POLISH ACAD SCIENCES, INST ENVIRON ENG PAS, 2016)
This study is aimed to investigate culturable airborne bacteria concentrations and the composition of methicillin-resistant staphylococci in eleven different locations on the basis of specific activities conducted within different parts of the European side of Istanbul. The highest bacterial levels were observed at the Bakirkoy station (1 100 CFU/m(3)) while the second highest levels were found at the Bahcelievler station (1 040 CFU/m(3)) in October; the lowest levels (10 CFU/m(3)) were measured at other different stations (Atakoy, Yesilkoy). Fifteen methicillin- resistant isolates [Staphylococcus hominis (n=11), S. cohnii spp. cohnii (n=2), S. sciuri (n=1), S. capitis spp. capitis (n=1)] were identified. The disc diffusion method was used to identify the antimicrobial resistance of these isolates, it was observed that the most common resistance was to penicillin (P) (n=11), doxycycline (DO) (n=4) and tetracycline (T) (n=5). None of the isolates was resistant to imipenem, amoxicillin/clavulanic acid, vancomycin (IPM, AMC, VA). However, multiple antimicrobial resistance was found to be 26.7%. The results of this study revealed the importance of isolated methicillin-resistant staphylococci in the stations with densely active human population and traffic, for public health. As a result, the importance of resting along known shorelines, where culturable airborne bacteria concentrations are much lower, and its importance for human health have been emphasized.
Keywords: Antimicrobial resistance; Culturable airborne bacteria; European side of Istanbul; GIS; Staphylococcus sp; DAY-CARE-CENTERS; EDIRNE CITY; ANTIBIOTIC-RESISTANCE; INDOOR; URBAN; AIR; FUNGI; CONTAMINATION; MICROORGANISMS; HUMIDITY; Environmental Sciences & Ecology